Material Screw Testing ON Tail Rotor Drive Using 'D' Penetrant Testing Method - Susilawati Susilawati; Masri Bin Ardin; Rafi Anwar Syarif (VANOS Journal of Mechanical Engineering Education, 2021)
Non Destructive Testing is a method of inspection that used in aircraft maintenance. Penetrant test is one type of Non Destructive Test (NDT) which is applied to screw tail rotor drive material. The purpose of this study was to determine the presence of defects, cracks, or other discontinuities without damaging the object being tested or inspected. The design research of applying the penetrant test to screw tail rotor drive material containing ferrous (fe) used the 'D' method, which is by dipping the material into the penetrant liquid with a waiting time of 20 minutes, then cleaning it using water and an emulsifier and drying using an oven. Before the inspection is carried out, the material is sprayed with a developer with a waiting time of 10 minutes, then the material is checked for defects or not. The test results showed that there was no defect in the form of a crack, but found an indication that is included in the non-relevant indication, which is an indication of the shape or design of the material found in the screw section.